2001
DOI: 10.1074/jbc.m005555200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Deacylation in Activation of Substrate Hydrolysis by Drosophila Acetylcholinesterase

Abstract: Insect acetylcholinesterase (AChE), an enzyme whose catalytic site is located at the bottom of a gorge-like structure, hydrolyzes its substrate over a wide range of concentrations (from 2 M to 300 mM). AChE is activated at low substrate concentrations and inhibited at high substrate concentrations. Several rival kinetic models have been developed to try to describe and explain this behavior. One of these models assumes that activation at low substrate concentrations partly results from an acceleration of deace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
10

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 45 publications
(50 reference statements)
3
14
0
10
Order By: Relevance
“…Nevertheless, other studies have hypothesized that aphids, thrips, and probably some insects might have both AChE and BChE [95,105]. In relation to this, an analysis of substrate hydrolysis at different concentrations revealed that insect cholinesterase displays activation at low substrate concentrations similar to that of the vertebrate BChE but demonstrated inhibition at high substrate concentrations similar to the vertebrate AChE [89]. Moreover, Keane and Ryan [96] reported that the inhibitory activity of monoterpenes against electric eel AChE is similar to the effect of inhibiting insect AChE.…”
Section: Potential Targets: Mode Of Action Of Essential Oil Componentsmentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, other studies have hypothesized that aphids, thrips, and probably some insects might have both AChE and BChE [95,105]. In relation to this, an analysis of substrate hydrolysis at different concentrations revealed that insect cholinesterase displays activation at low substrate concentrations similar to that of the vertebrate BChE but demonstrated inhibition at high substrate concentrations similar to the vertebrate AChE [89]. Moreover, Keane and Ryan [96] reported that the inhibitory activity of monoterpenes against electric eel AChE is similar to the effect of inhibiting insect AChE.…”
Section: Potential Targets: Mode Of Action Of Essential Oil Componentsmentioning
confidence: 97%
“…Thus, the control of the activity of this enzyme is very important in determining the insecticidal capacity of natural or synthetic chemicals, with AChE consequently being the primary target of organophosphorus pesticides and carbamates [85,86] as well as of some essential oils and their components [38,49,87,88]. However, the AChE in resistant insects is able to change its active site or create new forms of the enzyme, in response to selective pressure after several years of the application of synthetic pesticides [86,[89][90][91][92][93][94][95][96][97][98].…”
Section: Potential Targets: Mode Of Action Of Essential Oil Componentsmentioning
confidence: 99%
“…These residues in both insect AChE and vertebrate AChE are thought to operate through non-polar and pelectron interactions with the leaving group of substrates, and when binding to inhibitors (Harel et al, 2000;Brochier et al, 2001). They have been mutagenised in vitro in the AChE of various species to study their effect on interaction with various substrates and inhibitors (http://bioweb.ensam.inra.fr/ESTHER/general?what=mutalign).…”
Section: Mutations In the P1 Subsite Interacting With The Substrate Lmentioning
confidence: 99%
“…Structural and mutational studies have shown that the anionic site of cholinesterases functions mainly in the first, enzyme acylation stage of the reaction (Shafferman et al, 1992;Ordentlich et al, 1995Ordentlich et al, , 1996Koellner et al, 2000;Harel et al, 2000;Brochier et al, 2001), particularly in the formation of the non-covalent transition state (Nair et al, 1994). Therefore, mutations of the key residues affect mainly K m rather than k cat .…”
Section: Mutations In the P1 Subsite (Corresponding To The Ache Anionmentioning
confidence: 99%